The paradox of intervention: Resilience in adaptive multirole coordination networks - Casper van Elteren; Vítor V. Vasconcelos; Mike H. Lees (Proceedings of the National Academy of Sciences, 2025)
Complex adaptive networks exhibit remarkable resilience, driven by the dynamic interplay of structure (interactions) and function (state). While static-network analyses offer valuable insights, understanding how structure and function coevolve under external interventions is critical for explaining system-level adaptation. Using a unique dataset of clandestine criminal networks, we combine empirical observations with computational modeling to test the impact of various interventions on network adaptation. Our analysis examines how networks with specialized roles adapt and form emergent structures to optimize cost–benefit trade-offs. We find that emergent sparsely connected networks exhibit greater resilience, revealing a security–efficiency trade-off. Notably, interventions can trigger a “criminal opacity amplification” effect, where criminal activity increases despite reduced network visibility. While node isolation fragments networks, it strengthens remaining active ties. In contrast, increasing a node’s connectivity (analogous to social reintegration) can unintentionally boost criminal coordination, increasing activity or connectivity. Failed interventions often lead to temporary functional surges before reverting to baseline. Surprisingly, stimulating connectivity destabilizes networks. Effective interventions require precise calibration to node roles, connection types, and external conditions. These findings challenge conventional assumptions about connectivity and intervention efficacy in complex adaptive systems across diverse domains.